Widespread Grounding Line Retreat of Totten Glacier, East Antarctica, Over the 21st Century. Issue 17 (31st August 2021) - Pelle, Tyler; Morlighem, Mathieu; Nakayama, Yoshihiro; Seroussi, Hélène
Abstract: Totten Glacier (TG), the primary ice discharger of East Antarctica, contains 3.85 m sea level rise equivalent (SLRe) ice mass and has displayed ocean‐driven dynamic change since at least the early 2000s. We project TG's evolution through 2100 in an asynchronously coupled ice‐ocean model, forced at the ocean boundaries with anomalies in CMIP6 projected temperature, salinity, and velocity. Consistent with previous studies, the Antarctic Slope Current continues to modulate warm water inflow toward TG in future simulations. Warm water (−0.5 – 1 ° C) accesses TG's sub‐ice shelf cavity through depressions along the eastern ice front, driving sustained retreat of TG's eastern grounding zone that cannot be captured in uncoupled models. In high emission scenarios, warm water overcomes topographic barriers and dislodges TG's southern grounding zone around 2070, increasing the rate of grounded ice loss 3.5‐fold (10–35 Gt/yr) and resulting in a total 4.20 mm SLRe loss by 2100. Plain Language Summary: Totten Glacier (TG), East Antarctica, has been losing ice mass and retreating as a result of warm ocean water melting the underside of this glacier. To simulate this glacier's future evolution in response to realistic ocean forcing, we combine an ice sheet model of TG with a newly developed East Antarctic ocean model configuration and run simulations through 2100. Consistent with previous modeling studies, we find that the strength of the Antarctic Slope Current controls the presence of warm water near TG in future simulations. Significant retreat is projected on TG's eastern and southern sectors. On the eastern side, warm ocean water flows directly along the transition of floating to grounded ice, causing sustained melt throughout the entire simulation in all experiments. In contrast, warm ocean water can only access and promote retreat of TG's southern sector in the strongest warming scenarios by 2070, significantly accelerating TG's rate of mass loss and resulting in a total sea level rise contribution of 4.20 mm by 2100. Key Points: Simulations of Totten Glacier (TG) over the 21st century are performed in a coupled ice‐ocean model A 3.5‐fold increase in grounded ice loss follows retreat of TG's southern grounding zone, resulting in a 4.2 mm sea level rise contribution Coupled model results capture the spatial distribution of ocean‐driven basal melting and lead to retreat on the eastern flank